Effects of Delta-Shaped Obstacles on the Thermal Performance of Solar Air Heater. (20th October 2011) - Bekele, Adisu; Mishra, Manish; Dutta, Sushanta
Abstract : An experimental investigation has been carried out to study the effect of delta-shaped obstacles mounted on the absorber surface of an air heater duct with an aspect ratio 6 : 1 resembling the conditions close to solar air heaters. This study encompassed the Reynolds number (Re) ranging from 3400 to 27600, longitudinal pitch of the obstacle (P l / e ) varied from 3/2 to 11/2, and relative obstacle height (e / H ) varied from 0.25 to 0.75. The relative obstacle transverse pitch ( P t / b ) = 7 / 3 and the angle of attack of flow on obstacle = 90 ° are kept constant during the whole experimentation. By comparing the heat transfer data obtained from the obstacle-mounted duct with that of smooth duct under similar geometrical and flow conditions, the obstacle-mounted duct enhances the heat transfer by 3.6-times at Re = 7276.82, P l /e= 3 / 2, and e / H = 0.75 .